Library Automation in University: A Literature Review - Ngozi, Anozie Stella (PREDESTINASI, 2020)
The library is a growing organism that requires consistent positive changes to address the issue of its users. The innovation and emergence of computers brought about a definite transformation in the public. Along these lines, mechanisation has turned into the need of great importance. Library computerisation not only enhances the picture of the library and staff, in addition furnishes extra administrations to the users with the current staff. Library automation in essential terms is the utilization of PCs and the utilization of PC based things and organizations for doing various library exercises and limits. This research illustrates a review of the literature on Library Automation in University and related aspects of the theme. Apart from the literature on library automation in the university libraries, the aspects of the study includes library orientation programme, comparative Study of library software, integrated library systems, libraries, image analysis, imaging systems, universities libraries, information storage & retrieval systems, information science, open source software, Information resources management, digital library system, Library and internet users, library administration, library use studies. Finally, it covers the literature published on library automation in the university libraries, staff attitude towards on library automation, staff opinion on library automation, users’ opinion on library automation and requirement of orientation program in the university libraries. The work also covers the impact of the automation on users, staff and library services, e-resources development and use of electronic resources.